Vitamin A in prevention and treatment of cancer - Carvalho, Ricardo; Islam, Muhammad; Mata, Ana; e Silva, Reyca; Paz, Márcia; Alencar, Marcus; Rolim, Hercília; Medeiros, Maria; e Sousa, João; Melo-Cavalcante, Ana Amélia (International Journal of Medicine, 2017)
Dietary components not only act as chemo preventive agents but also risk factors in the onset of cancer, which stimulating nutritional bal-ance in cancer or non-cancer populations. The supplementation of antioxidant compounds, such as vitamin A (Vit A) and few of its deriva-tives has been reported to alleviate the oxidative stress in cancer patients. This review focuses on sketching a current scenario on the Vit A role in cancer prevention and therapy. Therefore, we searched for published article on PubMed and Science Direct between 2014 and 2015. The search yielded 75 articles related to Vit A-mediated anti-oxidative or pro-oxidative effects in cancer patients. A low dose-mediated anti-cancer effect was observed with Vit A in some cancers. The clinical studies showed discrepancies between the low and high doses of Vit A in cancer. In conclusion, precautions are needed in taking Vit A and its derivatives, especially in cancer.